A Troubled North Caucasus: What`s Ahead? - V. V. Degoev (Vestnik MGIMO-Universiteta)
In the article the author revisits the neverending post-soviet discourse on the burning issue – the North Caucasus threats to Russia`s statehood. He ponders over the question whether the region is the source or just the exotic extension of the country`s troubles. Whatever the answer is prof. V. Degoev thinks it vital for the Kremlin to try its best to escape the worst-case scenario on the turbulent multiethnic periphery. This end, as he concludes, has to be achieved by carefully calculated combinations of systemic approaches and the ad hoc reaction to social conflicts fraught with the nation-wide consequences.